Local monitoring of flowering and fruiting of Jernang, Daemonorops species in Sumatra, Indonesia - LARS SCHMIDT; HIMMAH RUSTIAMI; IDA THEILADE (Society for Indonesian Biodiversity, 2019)
Schmidt L, Rustiami H, Theilade I. 2019. Local monitoring of flowering and fruiting of Jernang, Daemonorops species in Sumatra, Indonesia. Biodiversitas 20: 118-125. Phenology and fruit production recordings of Jernang (Daemonorops spp.) were conducted in southern Sumatra over two one-year periods. Flowering and fruiting of 64 individual clumps with 570 stems > 2 m and 43 clumps with 478 stems > 2 m respectively were recorded on a monthly basis. Results showed that flowering and fruiting of Jernang took place throughout the year with a peak in April and May and at low level in September to March. Duration of male inflorescences was 2-3 months. Fruits were usually harvested for resin 2-3 months after flowering. Sex ratio of clusters was about 1:1. Flowers and fruits were produced on vigorously growing stems that had reached canopy light exposure. Clusters consisted of from 2 to 36 stems. In some clusters, all stems bore reproductive organs; in others, only few stems had flowers or fruits. Female clusters had significantly more stems than male clusters, but male clusters produced more inflorescences than did females. About 80% of the clusters during the first year’s survey and 50% the second year produced flowers. The most vigorous male clusters produced more than 80 inflorescences with up to 15 on a single stem within a year. The highest producing female clusters produced 12 inflorescences in a year with up to five inflorescences and four infructescences per stem in a year. The data was primarily collected by trained local monitors. They knew the species well and were used to spot flowers and fruits. However, since the local monitors were also all Jernang collectors, they usually picked fruits before maturity, and the full development into mature fruits was thus interrupted.